Aktivitas Antifungi Air Perasan Bawang Merah (Allium ascalonicum L.) Terhadap Candida albicans Secara In Vitro - Nurhasanah Nurhasanah; Fauzia Andrini; Yulis Hamidy (Jurnal Ilmu Kedokteran, 2015)
Shallot (Allium ascalonicum L.) has been known as traditional medicine. Shallot which has same genus with garlic(Allium sativum L.) contains allicin that is also found in garlic and has been suspected has fungicidal activity toCandida albicans. It is supported by several researches. Therefore, shallot is suspected has antifungal activity too.The aim of this research was to know antifungal activity of shallot’s water extortion againsts Candida albicans invitro. This was a laboratory experimental research which used completely randomized design, with diffusion method.Shallot’s water extortion was devided into three concentrations, there were 50%, 100% and 200%. Ketoconazole 2%was positive control and aquadest was negative control. The result of this research based on analysis of varians(Anova), there was significant difference between several treatments and was confirmed with Duncan New MultipleRange Test (DNMRT) p<0,05, there was significant difference between 100% shallot’s water extortion with othertreatments, but there was no significant difference between 50% shallot’s water extortion with 200% shallot’s. Theconclusion was shallot’s water extortion had antifungal activity againsts Candida albicans with the best concentration100%, but it was lower than ketoconazole 2%.